STRUCTURI ORGANIZATORICE ȘCOLARE ÎN CHIȘINĂUL INTERBELIC - Xenofontov, Ion Valer (CEP USM, 2024)
În baza izvoarelor istorice inedite din arhivele din Republica Moldova și România, din presa de epocă, au fost analizate structurile organizatorice școlare din cel de-al doilea oraș al României întregite, Chișinău. A fost studiată implicarea autoritățile locale în procesul de organizare a învățământului. Comitetul Școlar Comunal al municipiului Chișinău, și format din oficialități, cadre didactice, părinți, monitoriza cu strictețe repartizarea financiară din bugetul administrației publice locale. La fel, în vizor erau activitățile extracurriculare, mobilitățile școlare în cuprinsul țării, reparația sau închirierea de localuri, asigurarea școlilor cu resurse energetice, materiale didactice etc. În vederea consolidării și mobilizării activității educaționale și culturale cadrele didactice și-au format asociații profesionale. O direcție de activitatea a asociaților cadrelor didactice era orientată spre acțiuni sociale, de ajutorare a membrilor acestora, de creare a condițiilor de agrement.

Based on the original historical sources found in the archives of the Republic of Moldova and Romania, of the period press, the school organizational structures in the second largest city of Romania, Chisinau, were analyzed. The involvement of local authorities in the process of organizing education was studied. The Municipal School Committee of the Chisinau municipality - made up of officials, teaching staff, parents - strictly monitors the financial allocation from the local public administration budget. In the same way, extracurricular activities, school mobility within the country, the repair or rental of premises, providing schools with energy resources, didactic materials, etc. were not eclipsed from the sights either. In order to consolidate and mobilize the educational and cultural activity, the teaching staff formed professional associations. One direction of the activity of the teachers’ associates was oriented towards social actions, helping the members, creating leisure conditions.
SCHOOL ORGANIZATIONAL STRUCTURES IN INTERWAR CHISINAU
Keywords: Comitet Școlar; educație; cadre didactice; Chișinău; Basarabia; România întregită; interbelic; School Committee; education; teaching staff; Chisinau; Bessarabia; entire Romania; interwar